2015
DOI: 10.1002/ejoc.201500292
|View full text |Cite|
|
Sign up to set email alerts
|

The Nugent Reagent: A Formidable Tool in Contemporary Radical and Organometallic Chemistry

Abstract: The vast range of reactions mediated by titanocene monochloride (Cp2TiCl, the Nugent reagent) in organic synthetic chemistry is reviewed. The power of the Nugent reagent in organic chemistry is demonstrated by its ability to promote and/or catalyse several efficient transformations under mild reaction conditions in the presence of several functional groups, in an environmentally friendly manner and with use of simple experimental procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 109 publications
0
39
0
Order By: Relevance
“…Interestingly, increase in intensity of the absorbance observed at 462 nm in Pyr 4 FAP (Figure (D)), which is derived from [Cp 2 TiCl], was not observed in Pyr 4 OTf (Figure (D)) and 0.2 M Pyr 4 FAP/THF (Figure (D)), suggesting that equilibrium reactions between [Cp 2 TiCl] and [Cp 2 TiCl(S)] (S: solvent), as shown in Eqs. (4) and (5), exist in addition to Eq. .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, increase in intensity of the absorbance observed at 462 nm in Pyr 4 FAP (Figure (D)), which is derived from [Cp 2 TiCl], was not observed in Pyr 4 OTf (Figure (D)) and 0.2 M Pyr 4 FAP/THF (Figure (D)), suggesting that equilibrium reactions between [Cp 2 TiCl] and [Cp 2 TiCl(S)] (S: solvent), as shown in Eqs. (4) and (5), exist in addition to Eq. .…”
Section: Resultsmentioning
confidence: 99%
“…Such a redox equilibria are known from electrochemical studies of Cp2TiCl2 [41,42]. It was found that dependent on the cyclopentadienyl ring substituents, the intermediate radical anion might either reversibly split off a chloride anion yielding Cp2TiCl (the so-called "Nugent-Rajanbabu-reagent" [43]) or irreversibly one of the cyclopentadienyl ligands to give CpTiCl2. It was also reported that treatment of the dialkyltitanocenes Cp2TiR2 with organolithium compounds first produced unstable "back-onium complexes" [Cp2TiR3] − Li + , which decomposed at 20 °C to CpTiR2, RH, and LiCp [23].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] With these inspiring works, Cp 2 Ti III Cl has become a powerful tool for the development of new, highly enabling synthetic methodologies in contemporary radical chemistry. [16][17][18][19][20][21] In general, this reagent has been generated via chemical reduction of Cp 2 TiCl 2 with stoichiometric reductive metals such as metallic manganese or zinc and can be obtained as a green crystalline powder. The structure of Cp 2 Ti III Cl in solution was studied and proposed to be the equilibrium of dinuclear 1 and mononuclear 2 species.…”
Section: Introductionmentioning
confidence: 99%